Cancer Biomarkers in Body Fluids : Biomarkers in Circulation - Dakubo, Gabriel D. (Springer, 2017)
This book examines in depth the evidence, clinical applications and potential cancer signatures in the circulation and discusses alterations in circulating cell-free nucleic acids, and circulating tumor DNA, as well as the epigenome, genome, transcriptome (coding and noncoding), proteome (both traditional serum proteins and proteomic profiles) and metabolome. Further, it highlights the clinical applications of circulating tumor cells for each cancer type and addresses the emerging importance of extracellular vesicular contents, including miRNA, oncogenes and drug resistant factors. As such, it offers a valuable reference guide for cancer researchers, oncologists, clinicians, surgeons, medical students, oncology nurses, diagnostic laboratories, and the pharmaceutical industry.
Keywords: Cancer -- Molecular diagnosis.; Cancer -- Genetic aspects.; Biochemical markers.; elektronické knihy; electronic books